DIGITAL AGRICULTURE - THE CASE OF AUTONOMOUS PROVINCE OF VOJVODINA - Vukadinovic, Simonida; Jesic, Jelena Slavko; Okanovic, Andrea; Lovre, Ivan (Economics of Agriculture, 2022)
Agriculture as a crucial economic sector has changed rapidly in the last few decades, more than in previous centuries, because of technological achievements that opened a niche in the international agricultural sector known as digital agriculture. The conception of digital agriculture in practice and consequences on agricultural productivity is a way to response to significant climate changes. The evaluation of the current circumstances is made through the cases of digital agricultural companies in Vojvodina which could help and enhance regional economic growth. This study has utilized a case study method to evaluate the present conditions of digital agriculture appliances in Vojvodina. The results of the research will be a case study analysis of the companies using and developing digital agriculture technologies in the agricultural sector, as well as the presentation of potentials in this niche - digital agricultural sector in the Autonomous Province of Vojvodina. The authors of the paper consider the suggested model in this sector a vehicle that could run not only the economic growth in Vojvodina and Serbia, but also the regional economic growth.